2020
DOI: 10.1080/17843286.2020.1773653
|View full text |Cite
|
Sign up to set email alerts
|

Developing and evaluating a participatory arts programme for cancer patients and their caregivers

Abstract: There are several places in Belgium where cancer patients, survivors, and caregivers can turn to. The existence and expansion of these "drop-in" centres shows there is a high need for support and guidance before and also after cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Our research group previously conducted a survey on the acceptability and preferences of patients and caregivers on acupuncture as a complementary therapy for cancer care at the day clinic of the Kortrijk Cancer Centre [ 11 ]. Furthermore, within our cancer centre, we installed an art therapy programme taking into account the preferences of the patients and their caregivers [ 12 ].…”
Section: Psychosocial Oncology and Complementary Therapiesmentioning
confidence: 99%
“…Our research group previously conducted a survey on the acceptability and preferences of patients and caregivers on acupuncture as a complementary therapy for cancer care at the day clinic of the Kortrijk Cancer Centre [ 11 ]. Furthermore, within our cancer centre, we installed an art therapy programme taking into account the preferences of the patients and their caregivers [ 12 ].…”
Section: Psychosocial Oncology and Complementary Therapiesmentioning
confidence: 99%
“…Primary studies of group creative arts interventions have been carried out within specific creative arts therapies, most notably in music therapy (Potvin et al, 2018) and art therapy (Lang and Lim, 2014). Creative arts modalities used in interventions can be delivered sequentially such as art making followed by a drama workshop (Lefebvre et al, 2020), or combined, e.g. drawing and writing to music (Booth, 2006;Grocke and Wigram, 2007).…”
Section: Positive Impact Of Group Creative Arts Interventions For Car...mentioning
confidence: 99%
“…Participation in this study (94.5%) was high, likely because of the process of data collection used. A previous study by our research group implementing a survey found participation rates within this context could be low [28]. Therefore, a healthcare worker completed surveys with respondents.…”
Section: Study Population and Designmentioning
confidence: 99%